(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article explores the history of becoming, formation, development trends of medieval bazaars and shopping complexes in the cities of the Central Asian republics. A model of their formation is compiled. The analysis covers the list of trade and market facilities in Central Asian cities: an open bazaar, a street bazaar attached to it with shopping malls, a bazaar at the crossroads of «Chorsu» streets, covered shopping facilities («tim», «tokhi»), caravanserais , shopping malls, trade and craft suburb- “rabad”.